The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3389/fneur.2021.653752
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Circulation Time Is a Potential Predictor of Disabling Ischemic Cerebrovascular Events in Patients With Non-disabling Middle Cerebral Artery Stenosis

Abstract: Patients with non-disabling middle cerebral artery (MCA) stenosis (ND-MCAS) are at risk for disabling ischemic cerebrovascular events (DICE) despite aggressive medical therapy. In this study, we aimed to verify whether cerebral circulation time (CCT) was a potential predictor of DICE in patients with ND-MCAS. From January 2015 to January 2020, 46 patients with ND-MCAS treated with aggressive medical therapy were enrolled for digital subtraction angiography (DSA) in this convenience sampling study. They were di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 32 publications
(37 reference statements)
0
6
0
Order By: Relevance
“…However, it is yet unclear whether these factors could be used as predictors for stroke outcome ( Donkel et al, 2019 ). Also it is unknown whether they have additional value above other known prognostic factors in stroke ( Deng et al, 2018 ; Li et al, 2019 , 2020 ; Chang et al, 2021 ; Chen et al, 2021 ; Montellano et al, 2021 ). Female sex hormones can influence hemostatic factors causing the hemostasis system to function differently for men and women ( Abou-Ismail et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, it is yet unclear whether these factors could be used as predictors for stroke outcome ( Donkel et al, 2019 ). Also it is unknown whether they have additional value above other known prognostic factors in stroke ( Deng et al, 2018 ; Li et al, 2019 , 2020 ; Chang et al, 2021 ; Chen et al, 2021 ; Montellano et al, 2021 ). Female sex hormones can influence hemostatic factors causing the hemostasis system to function differently for men and women ( Abou-Ismail et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, (1) CCT was found to be correlated with prognosis for patients with subarachnoid hemorrhage: longer CCT predicted poorer outcome 24 ; (2) prolonged CCT is an independent prognostic factor for the occurrence of disabling ischemic cerebrovascular events in patients with symptomatic nondisabling middle cerebral artery stenosis. 17 Furthermore, Cronqvist et al found that CCT was more sensitive than the diffusible isotope technique for detecting the decreased flow associated with occlusive vascular disease. 40 …”
Section: Discussionmentioning
confidence: 99%
“…CCT based on ultrasound has been reported to be substantially prolonged in patients with multiple sclerosis or dementia, compared with controls. 15 , 16 CCT based on quantitative digital subtraction angiography (DSA) was found to be associated with the occurrence of disabling ischemic cerebrovascular events in patients who are not disabled, with symptomatic middle cerebral artery stenosis 17 and cerebral vasospasm in patients with subarachnoid hemorrhage. 18 Furthermore, cerebrovascular reserve as an independent risk factor for cerebral infarction 19 , 20 , 21 was found to be related to CCT derived from DSA.…”
mentioning
confidence: 99%
“…Cerebral circulation time (CCT) is confirmed to be an important parameter of cerebral blood flow reserve, which reflects the hemodynamic differences between symptomatic and asymptomatic carotid stenosis, hyperperfusion after carotid artery stenting and prediction of acute ischemic stroke in patients with middle cerebral artery stenosis. [1][2][3] It was first proposed by Greitz to be calculated on digital subtraction angiography (DSA) by measuring the time interval from visualization of the intracranial arteries to clouding of the cortical veins. 4 However, CCT lacks a unified evaluation method.…”
Section: Introductionmentioning
confidence: 99%